Population analysis of Tapes decussata (Bivalvia: Veneridae) in Lake Timsah, Suez Canal, Egypt - El-SayedKandeel, Kandeel (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The population of Tapesdecussatawas abundant in the southern region of Lake Timsah. It was investigated between August 2004and September 2005. Mean abundance and biomass were 76.9 ind.m-2 and 5.33 g.m-2 (flesh dry weight), respectively over the study period (n=14). Population parameters (growth, mortality and recruitment) were studied by analyzing monthly length frequency data using FiSAT ll software to evaluate the status of the stock. Asymptotic length (Lâˆž) was found to be 50.40mm and growth co-efficient (K) was 0.810 yr-1. The growth performance index (Ï•) was 3.31. Total mortality (Z) was estimated by length-converted catch curve at 2.52yr-1, fishing mortality (F) at 1.24yr-1, and natural mortality (M) at 1.28yr-1. The exploitation rate (E= 0.49 yr-1) indicated that the fishing pressure onTapesdecussata was relatively high. Recruitment pattern was continuous with four pulses per year. These pulses were found to be correlated with the spawning pattern of the species in Lake Timsah.